Ultrastructure and tube formation in Ceriantharia (Cnidaria, Anthozoa) - Stampar, Sérgio Nascimento [UNESP]; Beneti, Julia Silva; Acuña, Fabian H.; Morandini, André Carrara (Elsevier, 2015)
Cnidomes are an important feature that diagnoses groups of Cnidaria. Our paper describes how these structures are used in the formation of the tubes of tube Anemones, Ceriantharia. The structure of the tube was observed using SEM and the organization of the tubules are described for members of the three families of Ceriantharia. Additionally, the mode of production of the tube from animals that had their tube removed is described.
Keywords: Morphology; Behavior; Marine products; Tube Anemones; Morfologia; Comportamento animal; Bioprodutos marinhos